Konsep Proses Belajar Kognitif dalam Pespektif Islam antara Kontradiksi dan Kontradistingsi dengan Konsep Pembelajaran Kognitif Model Barat - Kajin, Sudar (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2018)
Accepting the role for cognitive transmission means recognizing that humans are not empty slate at birth. The basic assumption is that every human being is born by bringing fitrah and equipped with various potentials and abilities that are different from other humans. With that provision, he then learns: first through things that can be sensed by using his five senses as a window of knowledge; then gradually from things that can be sensed to the abstract, and from what can be seen to be understood. This study aims to describe the concept of cognitive learning processes in Islamic perspectives between contradictions and contradictions with the western cognitive learning concept. From the results of the discussion it was concluded that: cognitive learning and teaching are more responsive to the power of their instincts because they are purely related to the ability to develop rational abilities (reason). Many found contradictions and defects in their theories, so that revisions and emerging new theories of cognitive succession. While in Islam there is only one verse "And Allah takes you out of your mother's stomach in a state of not knowing anything, and He gives you hearing, sight and heart, so that you are grateful" (An Nahl: 78) is able to break the concept of response to the instinctive power in terms this is called scular and in Islam there has never been a secular tradition that separates religion from life